The Environmental Politics and Policy of Western Public Lands - Wolters, Erika Allen; Steel, Brent S. (Open textbook library., 2020)
In this volume, Erika Allen Wolters and Brent Steel have brought together the experts who can explain the evolution of public lands policies and politics in all their complexities. While their subject is complex, their prose is clear, and while their subject is torn by some of the most viciously self-interested, deceitful arguments in politics today, their prose is calm, factual, and evenhanded. No one should underestimate what a rare and valuable gift this is.